Rekonstruksi Maqasid Al-Syariah dalam Penanggulangan Deforestasi dan Kebakaran Hutan di Indonesia : Perspektif Hifz Al-Bi’ah Sebagai Etika Ekologis Islam - Andi Eril; Hayyul H; Kurniati Kurniati (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
Deforestation and forest fires in Indonesia are ecological problems that have a wide impact on the environment, public health, and sustainable development. Various countermeasures through positive legal instruments have been made, but they still face limitations because they tend to be formalistic and do not touch the ethical dimension. In the context of religious communities, religious values have strategic potential as a source of public ethics in preserving the environment. This study aims to analyze the reconstruction of maqāṣid al-syarī'ah in the management of deforestation and forest fires in Indonesia through the perspective of ḥifẓ al-bī'ah as an Islamic ecological ethics. This research uses a qualitative approach with the type of library research. Normative-philosophical and conceptual approaches are used to examine the sources of Islamic law, classical and contemporary maqāṣid al-syarī'ah thought, and Islamic environmental ethics literature relevant to the issue of deforestation. The data was analyzed descriptive-analytically to relate the concept of maqāṣid al-syarī'ah to the reality of the environmental crisis in Indonesia. The results of the study show that the crisis of deforestation and forest fires is not only a legal and policy issue, but also reflects an ethical crisis in the relationship between humans and nature. The reconstruction of maqāṣid al-shari'ah through the strengthening of the concept of ḥifẓ al-bī'ah emphasizes that environmental protection is a fundamental prerequisite for the realization of other shari'a goals. Thus, ḥifẓ al-bī'ah can be positioned as a relevant framework of Islamic ecological ethics to strengthen the fight against deforestation and forest fires in Indonesia and support sustainable development.